2022
DOI: 10.1039/d1en00735a
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput transcriptomics reveals the mechanisms of nanopesticides – nanoformulation, commercial formulation, active ingredient – finding safe and sustainable-by-design (SSbD) options for the environment

Abstract: Nanoformulations are developed to offer controlled release of active ingredients (a.i.) and thus aim to keep functionality while having a smaller environmental footprint. This means that nanoformulations aim to comply...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Such a response pattern has been also observed with other chemicals such as phenanthrene (Roelofs et al, 2016), nickel (Gomes et al, 2019a), and silver nanomaterials (Gomes et al, 2017), but not for all, e.g. copper nanomaterials (Gomes et al, 2018) or atrazine, including its nanoformulation (Gomes et al, 2021). Such a dose-dependent increase in the number of DEGs was not observed for E. albidus when exposure to Zn increased from EC50 to EC90 (Novais et al, 2012a).…”
Section: Gene Expressionmentioning
confidence: 67%
See 1 more Smart Citation
“…Such a response pattern has been also observed with other chemicals such as phenanthrene (Roelofs et al, 2016), nickel (Gomes et al, 2019a), and silver nanomaterials (Gomes et al, 2017), but not for all, e.g. copper nanomaterials (Gomes et al, 2018) or atrazine, including its nanoformulation (Gomes et al, 2021). Such a dose-dependent increase in the number of DEGs was not observed for E. albidus when exposure to Zn increased from EC50 to EC90 (Novais et al, 2012a).…”
Section: Gene Expressionmentioning
confidence: 67%
“…for silver (Gomes et al, 2017) and copper nanomaterials (Gomes et al, 2018)). On the other hand, for nickel (Gomes et al, 2019a) and atrazine (Gomes et al, 2021), a higher transcriptional response was observed after 7 days compared to 3 days. Although the gene/molecular responses precede the effects at higher levels of biological organization, the temporal pattern can be chemical specific, besides species specificity (Novais et al, 2012a).…”
Section: Gene Expressionmentioning
confidence: 85%
“…Soil microbial community maintenance depends on their homeostatic ability to face the complexity of exogenous environmental changes and disturbances, , such as nanoenabled pesticides and biopesticides. , The effect of these materials on soil microbiota can be evaluated by the strength of connectivity among elements interacting in a biological network such as the approach proposed by Amzallag. , A systemic approach was used to evaluate the global connectance of the soil microbial community ( Cg Total ). The Cg Total results revealed a decline in the stability of the microbial community, as can be seen, by the reduction in connection strength among the evaluated parameters (Figure ).…”
Section: Resultsmentioning
confidence: 99%